2017
DOI: 10.4335/15.3.647-668(2017)
|View full text |Cite
|
Sign up to set email alerts
|

Does Decentralized Governance Lead to Less Scientific Output? A Fuzzy Set Analysis of Fiscal Decentralization and Determinants of National Innovation Capacity

Abstract: his paper argues that national innovation infrastructure is closely linked with the scientific output and that some other factors, such as decentralized governance, can in certain combinations with innovation infrastructure lead to a higher scientific output. It demonstrates this by using a set-theoretic fsQCA method to analyze the data on national innovation capacities, fiscal decentralization, and science policy output. Results confirm that while a national innovation infrastructure is a necessary condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results also confirm the existence of spatial spillover for carbon emissions between regions and confirm the necessity and effectiveness of using spatial panel model analysis. This conclusion agrees well with Zhang et al (2011, Huang and Zhou (2014), Bellofatto and Besfamille (2015), Zupan et al (2017) and Zheng (2017). Fiscal decentralization reflects the degree of financial autonomy of local governments (Farzanegan and Mennel, 2012).…”
Section: Effects Of Fiscal Decentralizationsupporting
confidence: 93%
See 2 more Smart Citations
“…The results also confirm the existence of spatial spillover for carbon emissions between regions and confirm the necessity and effectiveness of using spatial panel model analysis. This conclusion agrees well with Zhang et al (2011, Huang and Zhou (2014), Bellofatto and Besfamille (2015), Zupan et al (2017) and Zheng (2017). Fiscal decentralization reflects the degree of financial autonomy of local governments (Farzanegan and Mennel, 2012).…”
Section: Effects Of Fiscal Decentralizationsupporting
confidence: 93%
“…explored that the Chinese style fiscal decentralization made the environmental policy significantly promote carbon emissions, leading to a green paradox. Zupan et al (2017) revealed the green paradox of local government exists in environmental governance under the effect of fiscal decentralization. Brännlund et al (2017)reported evidence of a negative direct effect of institutional quality on growth in per capita CO 2 emissions, especially for the global and high-income samples (Runar et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Each voivodeship has its endogenous potential, which, in connection with the exogenous potential and the ability to respond to changes in the environment, may constitute an opportunity for development. Endogenous factors (specific, unique, and corresponding to a given local system [ 102 ]) are the main driving force of regional development [ 103 , 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vasylieva & Kasyanenko (2013) single out decentralization as one of the determinants of the country's innovative potential growth. Besides, Zupan, Pustovrh, & Cankar (2017), studying the decentralization impact on the state's innovative potential, point out that expenditure decentralization help to develop the infrastructure, which together with other economic factors, enables to provide the highest degree of the scientific and innovative activity. Singh (2018), analysing the regional disproportions and preconditions of the sustainable economic development in India, notes that the investment activity extension at the administrative formations level (especially in the innovative projects) acts as a trigger of the sustainable economic growth.…”
mentioning
confidence: 99%